Defining and naming the Kurdish issue: Institutions, opinion leaders and parties - Cevheri, Seda Gizem (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Uluslararası İlişkiler Anabilim Dalı, 2012)
Kürt sorunu tarihsel geçmişe dayanan, ekonomik, sosyal güvenlik , kültürel ve demokratik hak sorunları boyutu olan Türkiye'nin yalnız iç siyasetini etkilemekle kalmayan dış politikasını özellikle Ortadoğu ülkeleri, AB ve ABD ile ilişkilerini derinden etkileyen bir sorundur. Türkiye siyaseti açısından önemli olan Kürt sorunun çözülememesi, sorunun bir türlü tanımlanamamış ve adlandırılamamış olmasındandır. Bu nedenle Kürt sorununa farklı çevrelerce kabul edilebilecek genel bir tanımlama ve adlandırma yapılmasının sorunun çözümüne katkıda bulunacaktır. Tezin birinci bölümünde Kürt sorununun tarihsel geçmişi anlatılmıştır. Bu bölüm Kürt sorununun kısa bir tarihidir. Üç dönemden oluşan bu bölümde Osmanlı İmparatorluğu'nda Kürtler ve Kürt sorunu, Milli Mücadele Dönemi'nde Kürtler ve Kürt sorunu, Türkiye Cumhuriyeti'nde Kürtler ve Kürt sorunu anlatılmıştır. Kürt sorununun tarihsel gelişimine değinilmesinin ardından tezin ikinci bölümünde, Kürt sorunu tanımlanmaya çalışılmıştır. Kürt sorununu oluşturan unsurlar; yani güvenlik sorunu, sosyo-ekonomik sorunlar ve kültürel ve demokratik haklar sorunu bu bölümde incelenecektir. PKK terörü, Türkiye Cumhuriyeti'nin PKK terörünün bitirilmesine yönelik aldığı önlemler ve diğer devletlerin PKK ile ilişkisi gibi önemli alt başlıklar Güvenlik sorununu oluşturmaktadır. Sosyo- ekonomik sorunlar ise; göç, eğitim, çalışma ve gelir sorunlarını içermektedir. Kültürel ve Demokratik haklar sorunu ise, insan hakları ihlallerinin ve anti demokratik uygulamaların yarattığı sorunlardan oluşmaktadır. Bu başlıkların hepsi Kürt sorununun parçalardır. Kürt sorunun tanımlanmasının ardından tezin üçüncü bölümünde; Kürt sorunun siyasi partiler, devlet kurumları, sivil toplum örgütleri ve kanaat önderleri tarafından nasıl tanımlandığı, nasıl açıklandığı ve nasıl adlandırıldığı incelenmiştir. Bu kişiler ve kurumlar, Türkiye Cumhuriyeti'nin iç ve dış siyasetini yönlendirdikleri gibi, toplumu da yönlendirmektedirler. Kürt sorununun çözülebilmesi için bu kişi ve kurumların soruna bakış açıları anlaşılmalı ve sorunun çözümü için ortak bir tanımlama yapılması sağlanmalıdır. Bu tez Osmanlı İmparatorluğu'nun Kürdistan coğrafyasınıda hâkimiyet kurmasından AKP önderliğinde Kürt sorununun çözümü için politika üretme çalışmalarının durduğu 2009 yılına kadar geçen sürede yaşananları referans almıştır. Farklı bakış açılarındaki kişi ve kurumların Kürt sorununa ilişkin görüşleri incelenerek hazırlanan bu tezin genel amacı; Kürt sorununun çözülmesi için toplumun farklı bakış açılarına sahip bütün kesimleri tarafından kabul edilecek bir adlandırma ve tanımlama yapılması gerektiğine dikkat çekmektir. Çalışma Kürt Sorununun birden fazla şekilde tanımlandığını ve adlandırıldığını, sorunun çözümü için tek bir tanımlama ve adlandırılma yapılması gerektiğini göstermiştir.

The Kurdish issue is a problem which is based on a historical background, have dimensions of economical, social, security and cultural and democratic right problems. The problem not only affects the domestic policy of Turkey but also the foreign policy and especially deeply influences the relations of Turkey with the Middle East countries, the EU (European Union) and the USA (United States of America). The fact that the Kurdish issue which is important in terms of the Turkish politics remains unresolved is originating from the problem somehow not being defined and named. Therefore, a general definition and a general naming of the Kurdish issue which would be adopted by different societies will contribute to the resolution of the problem. In the first part of the thesis, the historical background of the Kurdish issue was explained. This part is a short history of the Kurdish problem. It will provide clues on how the Kurdish issue emerged and how the issue developed in today?s context. This part consist of three periods which are The Kurds and Kurdish issue in Ottoman Empire, the Kurds and Kurdish issue in National Struggle Period, the Kurds and Kurdish issue in The Republic of Turkey will be explained. Subsequent to mentioning the historical development of the Kurdish issue, in the second part of the thesis the Kurdish problem was tried to be defined. The constituents of the Kurdish issue, such as security dimension, socio-economic dimension and cultural and democratic rights dimensions was examined in this part. Important subheadings such as PKK (Kurdistan Workers? Party) terror, the precautions taken by the Republic of Turkey towards the elimination of PKK terror and the relation of other countries with PKK, comprise the Security dimension. The socio-economic dimension includes the immigration, education, labor and income problems. In case for the cultural and democratic rights dimension is comprised of problems caused as a result of violation of human rights and anti-democratic implementations. All of these headings are components of the Kurdish issue. After defining the Kurdish issue, in the third part of the thesis, how the Kurdish problem is defined, how it is explained and how it is named by political parties, government institutions, non-governmental organizations and opinion leaders was examined. As these people and institutions lead the domestic and foreign politics of the Republic of Turkey, they also guide their groups. In order to resolve the Kurdish issue, the perspectives of these people and institutions towards the problem should be comprehended and the making of a common definition for the resolution of the issue should be ensured. This thesis has taken the developments beginning from the period in which the Ottoman Empire established sovereignty over the Kurdistan geography, until 2009 when the policy production studies towards the elimination of the Kurdish issue under the leadership of the AKP (Justice and Development Party) ceased as references. The general purpose of this thesis, which was prepared by examining the opinions of people and institutions with different perspectives towards the Kurdish issue, is to contribute to the establishment of a general definition and naming which would be accepted by all parts of the society who have different perspectives for the resolution of the Kurdish issue. Within this thesis, in which the Kurdish issue, one of the most essential problems of Turkey, is examined, the opinions of the referenced people and institutions towards the Kurdish issue are present. The research have shown that the Kurdish issue is defined and named in more than one manner and a single definition and naming is necessary to be made for the resolution of the issue.
Kürt sorununu tanımlamak ve adlandırmak: Kurumlar, kanaat önderleri ve partiler
Keywords: Siyasal Bilimler; Tarih; Uluslararası İlişkiler; Kamu kuruluşları; Kürt sorunu; Kürtler; Osmanlı Devleti; PKK; Sivil toplum örgütleri; Siyasi partiler; Terör; Türkiye Cumhuriyeti; Political Science; History; International Relations; Public institutions; Kurdish question; Kurdish; Ottoman Empire; Nongovernmental organizations; Political parties; Terror; Turkish Republic